Assessment of Frequency on Railway Sleeper by Field Measurements and Static Analysis - Kusumawardani, Rini; Kusbiantoro, Arief; Ermansyah, Naufal Maulana; Andiyarto, Hanggoro Tri Cahyo (Universitas Negeri Semarang, 2022)
The train is a mode of mass transportation that is fast, efficient, and relatively affordable. To support the high demand for this mode of transportation, adequate infrastructure is also needed. The condition of this infrastructure must always be monitored so that the level of security and safety of rail transportation modes can always be in optimal conditions. One important component that requires regular attention and maintenance is the railway sleepers. In this paper, a finite element (FE) model was made of railway sleepers using ANSYS software. From the analysis on the FE model, it can be explored that the deformation and stress that occurs in the railway due to loading. In this study, vibration tests were also carried out on railway based on several types of passing trains. It aims to determine the frequency value based on the type of passing train. This research is the initial stage of a series of studies on structural health monitoring procedures on railroads.